Aktuelle MRT-Bildgebung des Knorpels im Kontext der Gonarthrose (Teil 2): Knorpelpathologien und deren Beurteilung - Huppertz, Marc Sebastian; Lemainque, Teresa; Yüksel, Can; Siepmann, Robert; Kuhl, Christiane; Roemer, Frank; Truhn, Daniel; Nebelung, Sven (Die Radiologie, 2024)
High-quality magnetic resonance (MR) imaging is essential for the precise assessment of the knee joint and plays a key role in the diagnostics, treatment and prognosis. Intact cartilage tissue is characterized by a smooth surface, uniform tissue thickness and an organized zonal structure, which are manifested as depth-dependent signal intensity variations. Cartilage pathologies are identifiable through alterations in signal intensity and morphology and should be communicated based on a precise terminology. Cartilage pathologies can show hyperintense and hypointense signal alterations. Cartilage defects are assessed based on their depth and should be described in terms of their location and extent. The following symptom constellations are of overarching clinical relevance in image reading and interpretation: symptom constellations associated with rapidly progressive forms of joint degeneration and unfavorable prognosis, accompanying symptom constellations mostly in connection with destabilizing meniscal lesions and subchondral insufficiency fractures (accelerated osteoarthritis) as well as symptoms beyond the “typical” degeneration, especially when a discrepancy is observed between (minor) structural changes and (major) synovitis and effusion (inflammatory arthropathy).
CRIS-Team Scopus Importer:2024-01-12
Keywords: Arthrosis; Articular cartilage; Disease progression; Imaging diagnostics; Magnetic resonance imaging